2008
DOI: 10.1158/1535-7163.mct-07-0553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial metabolism by methyl-2-cyano-3,12-dioxooleana-1,9-diene-28-oate induces apoptotic or autophagic cell death in chronic myeloid leukemia cells

Abstract: The initial success of the first synthetic bcr-abl kinase inhibitor imatinib has been dampened by the emergence of imatinib-resistant disease in blast crisis chronic myeloid leukemia. Here, we report that the novel triterpenoid methyl-2-cyano-3,12-dioxooleana-1,9-diene-28-oate (CDDO-Me) potently induced cytotoxicity in imatinibresistant KBM5 cells expressing the T315I mutation of bcr-abl (24-h EC 50 , 540 nmol/L). In long-term culture, CDDO-Me abrogated the growth of human parental KBM5 and KBM5-STI cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…The extrinsic apoptotic pathway is activated by members of the TNF family by recruitment of caspase-8 into the death receptor complex. Bcl-2 family members regulate the intrinsic Suh et al, 1999Suh et al, , 2003bIto et al, 2000;Konopleva et al, 2002Konopleva et al, , 2004Konopleva et al, , 2005Stadheim et al, 2002;Ikeda et al, 2003Ikeda et al, , 2005Place et al, 2003;Inoue et al, 2004;Zhang et al, 2004;Han et al, 2006;Ray et al, 2006;Samudio et al, 2006Samudio et al, , 2008Shishodia et al, 2006;Brookes et al, 2007;Koschmieder et al, 2007;Kress et al, 2007;Tabe et al, 2007Tabe et al, , 2010Elsawa et al, 2008;Riccioni et al, 2008;Ahmad et al, 2010;Bernstein et al, 2012 ER-positive and -negative breast cancer CDDO CDDO-Im CDDO-Me Suh et al, 1999;Lapillonne et al, 2003;Place et al, 2003;Honda et al, 2004;Hyer et al, 2005;Konopleva et al, 2006;Ling et al, 2007;Liby et al, 2008b;Kim et al, 2011 Ovarian cancer CDDO CDDO-Me CDDO-Im Suh et al, 1999;Melichar et al, 2004;Duan et al, 2009;Petronelli et al, 2009b;Gao et al, 2011b P...…”
Section: Mechanisms Of Growth Arrest and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The extrinsic apoptotic pathway is activated by members of the TNF family by recruitment of caspase-8 into the death receptor complex. Bcl-2 family members regulate the intrinsic Suh et al, 1999Suh et al, , 2003bIto et al, 2000;Konopleva et al, 2002Konopleva et al, , 2004Konopleva et al, , 2005Stadheim et al, 2002;Ikeda et al, 2003Ikeda et al, , 2005Place et al, 2003;Inoue et al, 2004;Zhang et al, 2004;Han et al, 2006;Ray et al, 2006;Samudio et al, 2006Samudio et al, , 2008Shishodia et al, 2006;Brookes et al, 2007;Koschmieder et al, 2007;Kress et al, 2007;Tabe et al, 2007Tabe et al, , 2010Elsawa et al, 2008;Riccioni et al, 2008;Ahmad et al, 2010;Bernstein et al, 2012 ER-positive and -negative breast cancer CDDO CDDO-Im CDDO-Me Suh et al, 1999;Lapillonne et al, 2003;Place et al, 2003;Honda et al, 2004;Hyer et al, 2005;Konopleva et al, 2006;Ling et al, 2007;Liby et al, 2008b;Kim et al, 2011 Ovarian cancer CDDO CDDO-Me CDDO-Im Suh et al, 1999;Melichar et al, 2004;Duan et al, 2009;Petronelli et al, 2009b;Gao et al, 2011b P...…”
Section: Mechanisms Of Growth Arrest and Apoptosismentioning
confidence: 99%
“…It is noteworthy that the induction of ROS may be selective, because CDDO-Im induces ROS and activates DNA damage signaling pathways in breast cancer cells containing a defective BRCA1 gene but does not induce ROS in nonmalignant breast epithelial cells . A few exceptions regarding the inability of CDDO-Me to generate ROS have been reported, because high concentrations of this SO may induce apoptosis or autophagy in imatinib-resistant chronic myelogenous leukemia cells by increasing ROS, depleting glutathione and thus disrupting mitochondrial function (Samudio et al, 2008). CDDO-Me also stimulates the production of ROS in pancreatic cancer cells, thereby increasing levels of the ZBTB10 specificity protein repressor and decreasing expression of pro-growth, -survival, and -angiogenesis genes (Jutooru et al, 2010).…”
mentioning
confidence: 99%
“…Specifically, the methyl ester derivative of CDDO (CDDO-Me), at cytotoxic doses, leads to depletion of mitochondrial glutathione, increased production of reactive oxygen species (ROS) and permeabilization of the mitochondrial inner membrane. [21][22][23][24] In addition, our previous work shows that CDDO and its derivatives mediate apoptosis in lymphoma cells through a novel mitochondria-mediated mechanism. 25 CDDO leads to mitochondrial protein thiol modification and the generation of mitochondrial protein aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, it has been observed that these compounds bind to the active cysteine residue in the proteins [16]. The key proteins that have been reported to be modulated by oleanane triterpenoids are Keap 1 [193,194], IKK, IkBa and NF-jB [164,166], JAK1 and STAT3 [165,195,196], PTEN [197], AKT [14,198,199], mTOR [200], ROS [201], DR5 and CHOP [202], GSK3b [203], cFLIP and VEGF [204,205], mitochondrial membrane potential [206], and cell cycle arrest [198,207,208]. In another study where transgenic LSL-Kras(G12D/+); LSL-Trp53(R127H/+); Pdx-1-Cre (KPC) mouse model of pancreatic cancer were fed with diet containing CDDO-Me or CDDO-ethyl amide, the rexinoid LG100268 significantly increased the survival of mice by 3-4 weeks [209] and prevented lung cancer development when fed with these terpenoids for 8 weeks [15].…”
Section: Synthetic Triterpenoidsmentioning
confidence: 99%